The bearing of the local government in the development of the sugar industry in Passi, Iloilo, 1964-1997. - Gomez, Kenneth Dorona; Pio, Francis John Palmes (1999.)
This study analyzes the development of the sugar industry in Passi and the essential role played by the local government in the industry's progress. It also delves into the issue of the industry's positive and negative effects in the local economy and politics of the Municipality of Passi., The study has three objectives. The first objective is to identify factors that determined the development of the sugar industry in Passi in both sugarcane farming and sugar processing. Secondly, it aims to analyze the bearing of the local government in the development of the sugar industry in the said municipality. Lastly, the study aims to analyze the economic and political effects of the development of the local sugar industry. The development of the sugar industry in Passi as manifested by the dramatic expansion of sugarcane plantations and the establishment of the sugar mill (New Frontier Sugar Corporation) in the locality was significantly due to the inherent physical characteristics of the municipality that are deemed as very favorable for the sound growth of sugarcane. These include fertile types of soils, favorable topography and climate, and an abundant supply of the crop's water requirements from the main bodies of water that traverse the municipality. Also, another vital factor which caused the dramatic expansion of sugarcane plantations in the locality was the stable and profitable status of the national sugar industry in the world market. The strong position of the sugar industry especially in the 1960s up to the 80s was due to the implementation of treaties and international agreements which allowed the Philippine sugar exports to penetrate the US market without the burdens of heavy tariff and tax impositions. The very reason of the sugar industry's profitability at that time had urged the local sugarcane planters and landowners in Passi to expand the land coverage of sugarcane plantations. The local government of Passi assumed a vital role in the local sugar industry's development. In the aspect of sugarcane farming, though the locality's geographical characteristics certainly favors and expanded cultivation of sugarcane, the industry's progress had been primarily determined by the supportive agricultural policies and infrastructure projects of the local government. The agricultural policies that the local government promulgated and implemented emphasized the importance of the local sugar industry in the municipality's economy.These policies prioritized the provision of significant technological inputs and know-how to the sugarcane farmers. Also, the local government extended financial structures such as credit facilities. The establishment of the sugar processing industry reflected by the operation of the New Frontier Sugar Corporation (in 1968) in the locality was realized through the efforts of the local government. The role was shown by the various resolutions, which encouraged the sugar mill investors to put up the mill in the municipality. In order to ensure the progress of the sugar processing industry, the local government framed and implemented policies which provided for the construction of necessary infrastructure such as roads and bridges to facilitate the transportation of sugarcane harvests from sugar farms to the mill. Moreover, in order to ensure the quality of processed sugar, the local government together with the Sugar Regulatory Administration implemented a strict standard control of the produced sugar. These had shown the vital role assumed by the local government in the development of the local sugar industry. The development of the local sugar industry produced varied effects in the local economy and politics. Positively, the progress of the local sugar industry caused the rise in the agricultural and industrial labor forces. This reflected the dramatic rise in the municipality's employment rate. Also, the development of the industry triggered the rise in the municipality's annual income, in terms of revenue generation. The industry had been a significant factor in the municipality's rise to the status of being one of the major sugar producing area in the province and in Region VI. However, the development of the local sugar industry effected negative effects. The progress of the industry triggered the concentration of wealth into the hands of the big landowners. The accumulation of wealth by the landlords had been further intensified by the prevalence of oppressive labor practices, which severed the ill plight of the sugar farm workers. The development of the sugar industry indeed had positively contributed to the progress of the municipality. Yet, its positive effects are only to a superficial level. The rise of the industry to prominence had even widened the gap between the local elite-- the big landowning class-- and the majority poor population consisting mostly of sugar farm workers. This was amidst the luxurious life of the local elite characterized by possession of huge tracts of land, outright domination of the leadership of local politics, and ownership of key industries and business establishments in the municipality.
Thesis (Undergraduate, Bachelor of Arts in Community Development) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Sugar Industry -- Passi, Iloilo